Nutritional Values Of Ahara In Samsarjana Krama - Lahari, S V N Shivananda; Shivakrishna, M (International Research Journal of Ayurveda & Yoga, 2020)
Ayurveda places special emphasis on Ahara(diet) believes that “healthy nutrition” nourishes the mind, body and soul. It is a science which has given importance to diet and regimen as a part of chikitsa. pathya Ahara has a major supportive role in the management of disease. Shodhana and Shamana are two treatment principles of Ayurveda. Panchakarma is Shodhana treatment which includes Vamana, Virechana, Vasti, Nasya, Raktamokshana. Every Panchakarma is done in three stages Poorva karma, Pradhana Karma, Paschat karma. All of these stages has been given its own importance and relevance. Paschat karma is mainly focused on strict sequential dietary regimen called “Samsarjana krama”. This starts with introduction of simple carbohydrates to the diet and ends with inclusion of multi nutrient dietary formulation and finally normal diet. During Samsarjana krama, advised diet essentially consists of nutritive and easily digestive preparations such as Peya, Vilepi, Akritayusha, Kritayusha, Akritamamsa rasa, kritamamsa rasa. Factors such as Agni, Agniavasta, Dosha, Dosha avasta, Dhatu, Vyadhi, Vyadhi avasta need to be considered before planning Samsarjana krama. Adaptation of this diet is specific to quantity, nutritive value’s like increase the power of Pachana(digestion), Deepana(appetizer), Hrudya(cordinal), Truptigna(pacifies thirst), Brumhaniya(strengthen) , Dhatu pusti (nourishment of different tissues) etc... of the individual. So, this work will focus on evaluating the importance and nutritional values of Peya, Vilepi, Yusha, Mamsa rasas.